India's Smart City Program: Challenges and Opportunities - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
India launched its National Smart Cities Mission (SCM) in 2015 with the goal of transforming urban areas into more inclusive, sustainable environments. The program was a response to the needs of a rapidly urbanizing population which requires a radical transformation of the built environment in order to realize a more prosperous and egalitarian society. A total tendered amount of 1.84 lakh crore (24.6 billion USD) has been approved under the project, with new developments receiving funding across the country. However, the SCM has so far failed to live up to its promise in a number of respects. It has disbursed its funding through a grant structure at odds with a national strategic vision for smart urbanization. Furthermore, by stretching the definition of "smart cities" nearly beyond recognition, it has become a catch-all umbrella for new government funding to urban projects, rather than a push to make India's cities digitized and more sustainable. This raises the question of whether it is appropriate for India to invest in smart cities right now, or whether this funding should instead go towards expanding the systems which provide essential basic services to the population first. Fortunately, the vision for the SCM can be modified in a way that new investments made under the program both meet the existing needs of the population and start building the foundation for a smarter, 21st century infrastructure. Indeed, this is necessary if the SCM and future urban development projects are to yield concrete benefits proportional to their costs.
Keywords: 330